Challenges in sun protection - Surber, Christian 1955-; Osterwalder, Uli 1953- (Basel : Karger, 2021)
In the early 20th century, tanned skin was associated with good health. However, people began to protect themselves against potential overexposure to avoid sunburns. Around 1945, the first sunscreen products became available. In the years to follow, a vast number of different sunscreen filters and frameworks regulating filter substances and preparations, and methods characterizing sunscreen products were developed. The perception regarding the tasks of sunscreen products changed several times - initially it was promoted as a lifestyle product, then as a skin cancer preventive means, and more recently also for anti-aging. Different purposes and the widespread use of these products have led to myriad studies and a wealth of information. In this volume, the editors present a current collection of information analyzing and discussing issues related to sunscreen products and their use. These include challenges regarding the ideal sunscreen product including filter selection and formulation issues, measurement methods, performance characterization, safety, and regulatory issues. Further papers address topics related to the use of sunscreen products in everyday life, in vulnerable cohorts and outdoor workers. Controversial topics such as environmental effects of sunscreen products and the risks and benefits of UV radiation in the context of skin cancer, vitamin D and cardiovascular and metabolic health are also covered.
Keywords: PROTECTORES SOLARES; FACTOR DE PROTECCIÓN SOLAR; LUZ DIURNA -- EFECTOS ADVERSOS; RAYOS ULTRAVIOLETA